STRATEGI MEMBELI Public Offering Initial (IPO) Di PASAR MODAL PERDANA INDONESIA - hendarsih, ida (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2017)
ABSTRACK        Capital markets play an important role for economic development as one source of external financing for business and investment vehicles for the community. In the capital market investors can invest by means of ownership of securities for the company. In general, people can buy or as an investor on shares offered by the company. Buying IPO shares should use a certain strategy. The research method used qualitative descriptive analysis in data collection techniques. Collecting data by collecting information contained in newspaper articles, books, or scientific papers on previous research. Initial Public Offering (IPO) is a stock offering in the primary market conducted by a company that wants to go public. Through the capital market, a company may sell its Initial Public Offering (IPO) Initial Public Offering (IPO) to the public in order to obtain funding sources for expansion activities or company operations. Being an investor or buying shares in the capital market is not enough to understand the mechanism of buying and selling securities transactions, both stocks and bonds and profit-loss invest. Especially as inestos IPO must know a certain strategy to avoid loss when after buying IPO. Key Word: STRATEGI, Public Offering Initial (IPO), Capital markets